A SEMIOTIC ANALYSIS OF SALADIN’S LEADERSHIP AND HUMANISM IN THE FILM KINGDOM OF HEAVEN - Try Akhmal Hidayat; Fakhrur Rozi (Journal Analytica Islamica, 2026)
The representation of leadership in historical and war films generally emphasizes military strength, struggles for power, and the victory of particular groups. Consequently, the human dimension of leadership, especially in representations of Muslim figures such as Salahuddin Al-Ayyubi, has received relatively limited attention in communication and film studies. This study aims to analyze the representation of leadership and humanistic values embodied by Salahuddin Al-Ayyubi in Ridley Scott’s Kingdom of Heaven (2005). The study employs a qualitative approach using Roland Barthes’ semiotic analysis to examine denotative, connotative, and mythical meanings. Data were collected through observations of scenes, dialogue, facial expressions, and visual settings in the Director’s Cut version of the film, with particular attention to the characters of Salahuddin Al-Ayyubi and Balian of Ibelin. The findings demonstrate that leadership is represented through the ability to make prudent decisions, protect the community, and prioritize civilian safety amid warfare. Salahuddin’s refusal to seek revenge, his respect for his opponents, and his granting of religious freedom to the inhabitants of Jerusalem reflect strong humanistic values. At the level of myth, the film constructs the idea that an ideal leader is measured not by military victory but by the ability to uphold justice, compassion, and human dignity regardless of religious or group affiliation. These findings indicate that Kingdom of Heaven functions not merely as historical entertainment but also as a medium for reflecting on humanistic leadership that remains relevant to contemporary humanitarian challenges.